Blood thiol status and erythrocyte glutathione-S-transferase in chronic kidney disease patients on treatment with frequent (daily) hemodialysis. (March 2014) - Galli, F.; Piroddi, M.; Bartolini, D.; Ciffolilli, S.; Buoncristiani, E.; Ricci, G.; Buoncristiani, U.
Abstract Background. Chronic kidney disease (CKD) is a condition of impaired homeostasis of blood thiols characterized by a severe hyperhomocysteinemia (HH) and abnormal expression of the red blood cell glutathione (GSH)-consuming enzyme GSH S-transferase (eGST) (Galli et al., Clin Chem 1999). The correlation between plasma Hcy and eGST recently identified by our group (Dessì et al., Amino Acids 2012) suggests a role of this detoxifying enzyme in the impaired thiol status of CKD treated with hemodialysis therapy (HD). This retrospective study is aimed at investigating whether frequent HD can alleviate these biochemical symptoms of CKD. Methods. Laboratory data of a population of 98 HD patients investigated for plasma Hcy and blood thiol status between 1999 and 2004 were examined. A frequent HD method carried out with a 2-h daily schedule (daily HD) (DHD) was compared with standard 4-h × 3/week protocol of HD (SHD) in either cross-sectional (n = 70 SHD vs. n = 28 DHD) and prospective A-B design (n = 18 SHD patients shifted to DHD). Results. The results demonstrate that DHD produces a better correction than SHD of the uremic retention solute Hcy as well as of Cys and Cys-Gly measured in plasma. Such a correction effect of DHD on HH correlates with that on the detoxification enzyme eGST and on pGSH. Conclusions. These findings point to a role of frequent dialysis in the depuration of uremic retention solutes that may interfere with thiol metabolism and redox in HD patients. These solutes may include substrates of eGST that await further investigation for molecular identification and better removal by more efficient dialysis therapies.